Dari Kentrung hingga Ken Palman: Pasang Surut Kesenian Kentrung Jepara, 1970-2021 - Alamsyah, Alamsyah; Maziyah, Siti; Angga, Vicky Very (Department of History, Faculty of Humanities, Diponegoro University, 2023)
This article discusses the development of kentrung art, a traditional art originating from a city on the north coast of Java, namely Jepara. Kentrung has been present to accompany the people of Jepara for a long time and has become one of the instruments in religious rituals in Jepara. In addition, kentrung is also one of the entertainment's communities. In the 1970s to 1980s, kentrung experienced its heyday because it was in great demand by the public. However, in subsequent periods, kentrung faced challenges threatening its existence. Using historical methods, this article examines the adaptation strategy of kentrung art in meeting the challenges of globalization which have brought popular skills to the masses. Apart from that, kentrung also has to face the problem of regeneration because apart from the lack of spectators, there are also very few young people who are interested in becoming kentrung artists. The situation is becoming increasingly threatening to the existence of kentrung because the Covid-19 Pandemic is hitting the world. The results of the research show that the government's commitment, in this case the region and the community, guarantees the sustainability of the kentrung arts. An example is the case of regeneration initiated by the Jungpara Foundation which later gave birth to a kentrung art group named Ken Palman. In addition to regenerating, they also packaged kentrung performances to be more contemporary to attract the public.